Features of MMR markers expression (MSH2, MSH6, MLH1, PMS2) in endometrioid adenocarcinoms of the endometria - Savchenko , P.V. (Морфологія / Morphologia / Morfologìâ, 2026)
Topicality. Endometrial adenocarcinoma is one of the most common malignant neoplasms of the female reproductive system, for which modern approaches to diagnosis are based on a combination of morphological and molecular genetic characteristics of the tumor. Of particular importance is the determination of the deficiency of the mismatch repair system (MMR) and microsatellite instability, which is associated with Lynch syndrome, the prognosis of the disease and the possibility of using targeted and immunotherapy. The purpose. To determine the features of the expression of MMR markers (MSH2, MSH6, MLH1, PMS2) in endometrioid endometrial adenocarcinomas depending on the degree of morphological atypism and to assess their value as additional prognostic and diagnostic criteria. Methods. A retrospective analysis of postoperative material from 60 cases of endometrioid adenocarcinoma of the endometrium obtained in the morphological department of the diagnostic center of Dnipro for the period 2021–2024 was conducted. Immunohistochemical study was performed on formalin-fixed and paraffin-embedded material using the Lab Vision Quanto and DAB Quanto Chromogen imaging systems according to the WHO classification (2020). The studied cases were divided into three groups depending on the degree of tumor differentiation: grade 1, grade 2 and grade 3. Results. The average age of the patients was 54.30±10.68 years in the grade 1 group, 58.80±9.04 years in grade 2 and 58.67±10.46 years in grade 3. It was found that MSH2 expression was observed in 93.3% of grade 1 cases, 90% in grade 2 and 50% in grade 3, while MSH6 expression was 93.3%, 86.7% and 46.7%, respectively. At the same time, the absence of MLH1 and PMS2 expression in grade 1 was 96.3%, decreasing to 63.3% in grade 2 and 23.3% in grade 3, which indicates an increase in the expression of these markers with increasing malignancy. Statistically significant differences in the expression of MMR markers between groups of different degrees of differentiation were found (p<0.001). Also, concordance of marker expression in pairs MSH2/MSH6 and MLH1/PMS2 was established. Conclusion. The need to use a panel of MSI markers: MSH2, MSH6, MLH1 and PMS2 in endometrioid endometrial adenocarcinomas as prognostic and diagnostic markers is argued.